Effectiveness of Trigger Point Manual Treatment on the Frequency, Intensity, and Duration of Attacks in Primary Headaches: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Falsiroli Maistrello, Luca; Geri, Tommaso; Gianola, Silvia; Zaninetti, Martina; Testa, Marco (Frontiers in Neurology, 2018)
Background: A variety of interventions has been proposed for symptomatology relief in primary headaches. Among these, manual Trigger Points (TrP) treatment gains popularity but its effects have not been investigated yet. Objective: the aim was to establish the effectiveness of manual TrP compared to minimal active or no active interventions in terms of frequency, intensity and duration of attacks in adult people with primary headaches. Methods: We searched MEDLINE, COCHRANE, Web Of Science and PEDro databases up to November 2017 for Randomised Controlled Trials (RCTs). Two independently reviewers appraised the Risk of Bias (RoB) and the Grading of Recommendations, Assessment, Development and Evaluation (GRADE) to evaluate the overall quality of evidence. Results: Seven RCTs that compared manual treatment vs minimal active intervention were included: 5 focused on Tension-Type Headache (TTH) and 2 on Migraine (MH); 3 out of 7 RCTs had high RoB. Combined TTH and MH results show statistically significant reduction for all outcomes after treatment compared to controls but the level of evidence was very low. Subgroup analysis showed a statistically significant reduction in attack frequency (n° of attacks per month) after treatment in TTH (MD -3.50; 95% CI from -4.91 to -2.09; 4 RCTs) and in MH (MD -1.92; 95% CI from -3.03 to -0.80; 2 RCTs). Pain intensity (0-100 scale) was reduced in TTH (MD -12.83; 95% CI from -19.49 to -6.17; 4 RCTs) and in MH (MD -13.60; 95% CI from -19.54 to -7.66; 2RCTs). Duration of attacks (hours) was reduced in TTH (MD -0.51; 95% CI from -0.97 to -0.04; 2 RCTs) and in MH (MD -10.68; 95% CI from -14.41 to -6.95; 1 RCT). Conclusion: Manual TrPs treatment of head and neck muscles may reduce frequency, intensity and duration of attacks in TTH and MH but the quality of evidence according to GRADE approach was very low for the presence of few studies, high risk of bias and imprecision of results.